A novel pendulum test for measuring roller chain efficiency. (29th May 2018) - Wragge-Morley, R; Yon, J; Lock, R; Alexander, B; Burgess, S
Abstract: This paper describes a novel pendulum decay test for determining the transmission efficiency of chain drives. The test involves releasing a pendulum with an initial potential energy and measuring its decaying oscillations: under controlled conditions the decay reveals the losses in the transmission to a high degree of accuracy. The main advantage over motorised rigs is that there are significantly fewer sources of friction and inertia and hence measurement error. The pendulum rigs have an accuracy around 0.6% for the measurement of the coefficient of friction, giving an accuracy of transmission efficiency measurement around 0.012%. A theoretical model of chain friction combined with the equations of motion enables the coefficient of friction to be determined from the decay rate of pendulum velocity. The pendulum rigs operate at relatively low speeds. However, they allow an accurate determination of the coefficient of friction to estimate transmission efficiency at higher speeds. The pendulum rig revealed a previously undetected rocking behaviour in the chain links at very small articulation angles. In this regime, the link interfaces were observed to roll against one another rather than slide. This observation indicates that a very high-efficiency transmission can be achieved if the articulation angle is very low.